Weed Control for Winter Faba Bean Cover Crop in South Florida - Dennis C. Odero (EDIS, 2011)
Faba bean is an important leguminous winter crop in warm temperate and subtropical areas that has been cultivated for more than 10,000 years as a source of protein in human and livestock diets. It is also grown to enhance yields of other crops. Faba bean provides nitrogen in agricultural systems through the unique process of biological fixation of atmospheric nitrogen by symbiosis with Rhizobium bacteria. This substantially reduces the need for nitrogen fertilizers, which contribute to both carbon dioxide and nitrous oxide emissions. This 2-page fact sheet written by D.C. Odero provides weed control recommendations. Published by the UF Department of Agronomy, April 2011.